Geodynamics and evolution of the Miocene mineralization in the Cycladic - Pelagonian belt, Hellenides - SKARPELIS, N. (Bulletin of the Geological Society of Greece, 2002)
The paper aims to provide a sound account of the type of Miocene mineralisations in the Cycladic – Pelagonian belt and their relationship with the geodynamic evolution of the area. Skarn and manto types, epithermal precious and base metals mineralisation, and vein magnesite in ultramafics are associated to distinct stages of the geodynamic evolution of the belt. Extensional tectonics favoured their generation. Late stages of extensional tectonics resulted in the formation of vertical to subvertical NW-SE trending fault zones, which were then used as conduits for ascending hydrothermal fluids. The relationship between the geodynamics and the metallogenetic evolution of the belt is discussed on the basis of available data on the geology of four critical areas: Tinos and Mykonos islands, Laurium and Northern Euboea.